RISK MANAGEMENT OF MICRO COOPERATIVES IN CAGAYAN VALLEY, PHILIPPINES - CAMMAYO, EVA U. (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to determine the strategies and policies of micro cooperative in Cagayan Valley, Philippines in the context of risk management. Specifically, it aimed to (1) determine the relationship between the levels of adoption of risk management practices and profitability; (2) compare the perceptions of members, staff and BODs on the levels of adoption of practices on risk management of micro cooperatives in Cagayan Valley, Philippines; (3) compare the financial performances of micro cooperatives among provinces in Cagayan Valley, Philippines and identify the most pressing problems encountered by micro cooperatives in Cagayan Valley, Philippines. Twenty two (22) micro cooperatives, selected purposively, were involved in the study. Descriptive correlation method was applied. The study suggests that the levels of adoption of cooperative risk management practices has no significant effect on profitability of micro cooperatives in Cagayan Valley, Philippines. All the three (3) groups of respondents agree that the level of adoption of cooperative risk management practices is “high”, unfortunately, the overall financial performances of all the micro cooperatives are unsatisfactory.